Management Practices Use by Schools to Improve the Attendance of Advanced Level (A/L) Students - Kumari, H.M.L.; Wickramanayake, R. (International Journal of Research and Innovation in Social Science, 2023)
The purpose of this study was to find out the strategies and measure taken by the school management and the teachers for boosting the attendance of Advance Level students. The study was focused to get an insight idea on student related factors for students’ poor attendance, to find out strategies use by teachers to minimize students’ poor attendance and to recommend suggestions to uplift students’ attendance. Concurrent mix methodology was adopted for the study and the data was collected by survey questionnaires and by interviews. The questionnaires were given both students and parents who selected randomly for the sample. The survey sample was consisted of 92 Advance Level students and 46 of their parents. 8 Advance Level class teachers were selected purposively for interviews. Descriptive statistical methods such as tables, graphs and percentages were used for analyzing and presenting quantitative data and thematic analysi swas used for analyzing data which gathered from interviews. The study revealed that major student related factors that caused for poor attendance were; attending tuition classes and negative peer pressure and less motivation. Other than that expecting just a pass from the A/L exam, less interesting to study in school are caused in minor level. Identifying the most absent students by checking students’ attendance books once a month, discussing with parents of absent students were the most of strategies that followed by school management for the particular situation. As the suggestions for uplifting attendance of students; covering the syllabi quickly in schools, starting revision classes, increasing co-curricular activities, starting to teach from middle of syllabi and regulating feedback classes and subject conferences could be found out by the study.
Keywords: Attendance; Type 1AB Schools; Advanced Level Education; Management Practices